KEBUTUHAN RUMAH DAN UPAYA PENYEDIAAN RUMAH BAGI WARGA MISKIN DI KOTA SEMARANG (Geo-Image, 2015)
This study aims (1) to projecting the housing needs for the poor in the Semarang City at the end of 2015 and 2016, and knowing its distribution in each district; (2) to know the effort to provide housing for the poor is done by the Government of Semarang City; (3) to know the perception of the efforts to provide housing for the poor is done by the Government of Semarang City. The method research used is the statistic descriptive and descriptive qualitative. The conclusions in this research are : 1) The housing needs for the poor at the end of 2015 as many as 65.448 unit and increased to as many as 67.555 units at the end of 2016, while the spatial distribution associates with a number of people and the poor; 2) Efforts to provide housing for the poor include drafting RP3KP, flats, home improvement uninhabitable and social assistance field of restoration the house is not livable community-based; 3) Based on special perception, the majority of aid was livable, except in towers Bandarharjo and the aid repair uninhabitable housing in the District of North Semaran. Based on the general perception, improvement of uninhabitable housing is not maximized due to the perceived rather badly.